DYNAMICS OF PHYSICAL FITNESS INDICATORS OF GIRLS AGED 6-14 PARTICIPATED IN TENNIS AND THEIR QUALITATIVE ASSESSMENT - Skorodumova, A.P.; Semenova, S.D.; Tarpishcheva, A.R.; Tarpishchev, F.Sh. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the magnitude of changes in the indicators of physical qualities in female tennis players aged 6-14 years. Methods and structure of the study. To assess the physical fitness of tennis players aged 6-14, training at the stage of initial training and the training stage, it was proposed to perform 18 tests, on the basis of which 21 indicators were calculated. A total of 228 girls aged 6-14 who go in for tennis at sports schools in Moscow and the Moscow region, as well as private academies and clubs, were examined. Results and conclusions. Achievements demonstrated by tennis players at 14 years old are better than at 6 years old. However, in some tests, the best results were recorded in tennis players under 14 years old. The scatter in the values ​​of the increase in results in different tests is large and ranges from 1.48% to 345.03%. The magnitude of the increase in the result in a test that evaluates physical quality largely indicates the degree of trainability of the quality. It has been established that in tests evaluating the same physical quality, there is a large scatter in the values ​​of the increase in results, which indicates a different degree of trainability of manifestations of the same quality.